Performance of short piled raft foundation system on peat soil under static load - Marto Suro, Sajiharjo (2020)
Peat is known as problematic soil, because has low shear strength and high compressibility characteristics. Particular attention should be paid, when building a construction on it. In recent years, there is no special established foundation structure for peat yet, without any treatment of soil. Thus, notably for a depth of 3 to 10 m of the peat layer, there is a challenge to develop a foundation system on peat without any stabilization nor remove and replace, especially for foundation under static point load. This research was conducted to explore a proposed Short Piled Raft (SPR) foundation system, which is a combination of a pile foundation and raft foundation, with a pile length short enough. The objectives of this research were to optimize pile spacing of SPR foundation system related to its stability, especially immediate settlement. The optimization was carried out by comparing some results of simulation using Plaxis 3D Foundation software for numerical modelling. The software was also used for another simulation series with some different soil parameters and site conditions. The selected results of numerical modelling were verified by using the full scale model. Optimum pile spacing of the SPR foundation system with the pile length of 3.0 m and pile outer diameter of 0.32 m is 1.0 m. It was found that SPR foundation system has superiority than other previous methods (Chicken Claw and Nailed Slab). The main reason is that SPR has weight relatively lighter than others, caused by utilizing the uplift force to closed end pipe as pile and the thin concrete slab. While for loading test of full scale model of 3.0 m x 3.0 m concrete slab with the thickness of 0.15 m and 9 closed end short piles, the result shown a good performance. The SPR was able to support 100% design load of 100 kN, with maximum immediate settlement was 19 mm and for 160% design load, maximum immediate settlement was 34 mm. The knowledge contribution of this research is a proposed chart for basic step to design SPR. With these findings, it is hoped that the next research is recommended to research stability of the SPR on peat under static load in the long term and also for dynamic load.